Evaluation of dye aggregation and effect of deoxycholic acid concentration on photovoltaic performance of N749-sensitized solar cell - Bang, So Yeon; Ko, Min Jae; Kim, Kyungkon; Kim, Jong Hak; Jang, In-Hyuk; Park, Nam-Gyu (ELSEVIER SCIENCE SA, 2012)
Black dye, coded N749, solutions with different concentration of deoxycholic acid (DCA) were prepared and effect of DCA concentration on photovoltaic property was investigated. Photocurrent density was improved by addition of DCA ranging between 2 mM and 20 mM, while little changes in voltage and fill factor were observed. High concentration of 100 mM DCA, however, deteriorated photovoltaic performance due to the significant decrease in photocurrent density. Photocurrent density of 15.6 mA/cm(2) observed without DCA was improved to 16.5 mA/cm(2) after addition of 10 mM DCA in N749 solution, while the amount of the adsorbed dye was decreased from 60.9 mmol to 51.3 mmol per cubic centimeter of TiO2. Based on changes in photocurrent density and amount of the adsorbed dye, the faction of dye aggregation, which could not contribute to photocurrent generation, was estimated to be about 40%. The large fraction of dye aggregation was thus responsible for low photocurrent density, which could be resolved by addition of DCA. Based on an optimal condition of 10 mM DCA and 30-mu m-thick TiO2 film with light scattering layer, conversion efficiency of 9.1% was demonstrated at full sun illumination. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: COUMARIN-DYE; TIO2 FILMS; BLACK DYE; EFFICIENCY